Host plant resistance to insects in pulse crops - Togola, A.; Ongom, P.O.; Mohammed, S.B.; Fatokun, C.; Tamò, Manuele; Boukar, O. (Springer, 2024)
Pulses are important sources of protein, dietary fiber, vitamins, and minerals for human nutrition and are widely cultivated in many countries around the world. Crops belonging to pulse include mainly chickpeas, mung bean, lentils, pigeon peas, and cowpeas. Pulse production and storage are negatively affected by a variety of biotic and abiotic factors, such as insect pests, diseases, parasites, low soil fertility, heat, and drought. Among these, insect pests have the most significant impact on pulse productivity worldwide. The extent of insect pest damage is a major challenge for pulse farmers and can lead to significant quantitative and qualitative losses. While synthetic insecticides are commonly used to control insect pests in pulses, their harmful effects on humans, animals, and the environment, as well as the development of insecticide resistance in pests, have prompted research efforts to identify eco-friendly alternatives. One such alternative is host plant resistance, which involves developing pulses with genetic traits that make them resistant to insect pests. The chapter underlined the importance of host plant resistance as a sustainable approach to protecting pulse crops against insect pests. It reviews past and recent studies that have contributed to improving pulse crops and sustaining their production through host plant resistance measures. Genomic tools and resources could be further utilized to develop insect resistance in all types of pulses and accelerate the pace of research in this area.